(untitled) (Journal of the College of Basic Education, 2022)
The study of fertility measures is necessary when studying the population, whether at the geographical or demographic level, because fertility does not mean anything unless it is included in population censuses that give it statistical indications, and this is only done through the use of fertility measures because these standards serve several purposes, including that they are considered the basis for measuring the degree of fertility. Population change It is also the basis for setting population policies and health programs, and represents the basis for many population programs that flow into development plans. Through this importance, we have taken it as a topic for research, based on the results of the 1997 census, and the studies written about it, in line with the nature and purpose of the research.